Konsekuensi Yuridis Penyelesaian Kredit Macet dengan Proses AYDA (Agunan Yang Diambil Alih) oleh Bank Berdasarkan Undang-Undang Hak Tanggungan - Wulandari, Fitria Ajeng (Faculty of Law Universitas Islam Indonesia, 2024)
Banks often encounter obstacles in providing credit to debtors, such as bad debts. One solution to bad debts is for banks to take over collateral by purchasing the collateral and then reselling it to another party. There is a potential conflict between the Banking Law and the Mortgage Law, as the Mortgage Law only regulates collateral execution through general customers. If AYDA is carried out without an auction and without the debtor's consent, this could violate the principles of publicity and legal certainty. The type of research used is normative juridical, whose object is legal norms. The approach method used is a conceptual and regulatory approach, using primary, secondary, and tertiary legal materials collected through literature studies and analyzed qualitatively. The process of the Assumed Collateral (AYDA) can be considered null and void by law because the agreement to voluntarily hand over the collateral which is the basis for the Assumed Collateral (AYDA) does not comply with the fourth condition for the validity of an agreement as stipulated in Article 1320 of the Civil Code, namely